Role of STIM1 in the surface expression of SARAF - Albarran, Letizia (Channels (Austin), 2016)
The store-operated Ca(2+) entry-associated regulatory factor (SARAF), a protein expressed both in the endoplasmic reticulum and the plasma membrane, has been presented as a STIM1-interacting protein with the ability to modulate intracellular Ca(2+) homeostasis. SARAF negatively modulates store-operated Ca(2+) entry (SOCE) by preventing STIM1 spontaneous activation and regulating STIM1-Orai1 complex formation. In addition, SARAF is a negative regulator of Ca(2+) entry through the arachidonate-regulated Ca(2+) (ARC) channels. Here we explored the possible role of the surface expression of SARAF on the location of STIM1 in the plasma membrane. In NG115-401L cells, lacking a detectable expression of native STIM1, transfection with pHluorin-STIM1, which is able to translocate to the cell surface, enhances the plasma membrane location of SARAF as compared to cells transfected with YFP-STIM1, lacking the ability to translocate to the cell surface. These findings suggest that the surface location of SARAF is dependent on the expression of STIM1 in the plasma membrane.